Mother and transgendered son: a study of gender role conflict in Sherwood Anderson’s “mother” (BRAC University Journal, 2026)
In a conventional society men are expected to be masculine. Unlike women, they must be resolute, authoritarian and truculent. In comparison to men, women are presumed to exhibit feminine gender traits like submissiveness, compassion and obedience. However, if a discrepancy is found between a man/woman’s gender expression and his/her biologically assigned sex, then it is called GRC or Gender Role Conflict. GRC often leads to an inability to perform according to one’s assigned gender role. In addition to that Gender Role Conflict can also create transgender identities. Transgender individuals are physically of one gender, mentally of the other. When a man starts behaving like a woman, he is called a male-to-female or MtF transgender man. Since it is considered a violation of social standards, GRC creates difficulties in his social and family life. Nevertheless, proper guidance and assistance from friends and family members can aid him adequately. This issue is poignantly dealt by American author Sherwood Anderson in his story “Mother”. Here Elizabeth Willard is a “grotesque” suffering from a life-long gender role conflict. Her son George Willard is an MtF transgender man who endures similar conflicts throughout his life. When society wants George to fulfill his masculine duties, his mother recognizes the inherent woman in him. This paper will explore Elizabeth’s motherly empathy for her transgender son as it helps him to resolve his gender role conflict and inspires him to live a normal life.